NATURAL GAS MARKET DEVELOPMENT - IMPLICATIONS FOR DIVERSIFICATION OPTIONS OF EU: CASE STUDY OF SLOVAKIA - Mothana, Saleh Obadi; Korcek, Matej (European Scientific Journal, ESJ, 2014)
European Union has been exposed to major changes on global natural gas markets since beginning of 21.century. Shale gas, development, liberalization on Russian market accompanied by lower consumption due to economic crises and interconnecting of natural gas network created a matrix of interacting elements which can clearly influence energy security of EU. The aim of this article was to analyze how the global trends on natural gas market from recent years so far affected the EU natural gas market in terms of diversification with special focus being dedicated to Slovakia. We came to conclusion that shale gas has so far only indirect implications, LNG impact is limited and EU will be in the closest future affected mainly by Russian natural gas export politics. As case of Slovakia documents EU diversification efforts have not been successful so far and EU internal energy market suffers from policies distorting market environment.